Progressive Pentecostalism: an emergent trend in global Christianity - Miller, Donald E. (Journal of beliefs and values, 2009)
The emergence of Pentecostalism, its worldwide spread and its transformation of itself, in many places, into a religion of social engagement is described and analysed.